Can you hear me clearly? The differential effects of surgical mask on Cantonese consonant, vowel, and tone perception - Choi, William; Chu, Tianyu; Zu, Jiaqing (Frontiers in Communication, 2025)
This study examined the differential effects of surgical mask on Cantonese consonant, vowel, and tone perception. Forty native Cantonese adults were tested with the Cantonese consonant, vowel, and tone identification tasks. Each task contained four blocks: quiet-no mask, noisy-no mask, quiet-surgical mask, and noisy-surgical mask. Bayesian analyses revealed that the Cantonese listeners identified consonants, vowels, and tones with similar accuracies across the four blocks. However, in the presence of noise, surgical mask was found to increase the response time in identifying vowels. From a theoretical perspective, this study offers a phonological account to explain why surgical mask may impede sentence comprehension. Practically, the findings suggest that surgical mask has little bearing on the ability to accurately identify Cantonese consonants, vowels, and tones, though it affects the efficiency in vowel identification.